Methodological quality of systematic reviews on Chinese herbal medicine: a methodological survey - Andy K. L. Cheung; Charlene H. L. Wong; Leonard Ho; Irene X. Y. Wu; Fiona Y. T. Ke; Vincent C. H. Chung (BMC, 2022)
Abstract Background Systematic reviews (SRs) synthesise the best evidence of effectiveness and safety on Chinese herbal medicine (CHM). Decision-making should be supported by the high-quality evidence of prudently conducted SRs, but the trustworthiness of conclusions may be limited by poor methodological rigour. Methods This survey aimed to examine the methodological quality of a representative sample of SRs on CHM published during January 2018 to March 2020. We conducted literature search in Cochrane Database of Systematic Reviews, MEDLINE via Ovid, and EMBASE via Ovid. Eligible SRs must be in Chinese or English with at least one meta-analysis on the treatment effect of any CHM documented in the 2015 Chinese Pharmacopoeia. Two reviewers extracted the bibliographical characteristics of SRs and appraised their methodological quality using AMSTAR 2 (Assessing the Methodological Quality of Systematic Reviews 2). The associations between bibliographical characteristics and methodological quality were investigated using Kruskal-Wallis tests and Spearman's rank correlation coefficients. Results We sampled and appraised one hundred forty-eight SRs. Overall, one (0.7%) was of high methodological quality; zero (0%), four (2.7%), and one-hundred forty-three (96.6%) SRs were of moderate, low, and critically-low quality. Only thirteen SRs (8.8%) provided a pre-defined protocol; none (0%) provided justifications for including particular primary study designs; six (4.1%) conducted a comprehensive literature search; two (1.4%) provided a list of excluded studies; nine (6.1%) undertook meta-analysis with appropriate methods; and seven (4.7%) reported funding sources of included primary studies. Cochrane reviews had higher overall quality than non-Cochrane reviews (P < 0.001). SRs with European funding support were less likely to have critically-low quality when compared with their counterparts (P = 0.020). SRs conducted by more authors (r s  = 0.23; P = 0.006) and published in higher impact factor journals (r s  = 0.20; P = 0.044) were associated with higher methodological quality. Conclusions Our results indicated that the methodological quality of SRs on CHM is low. Future authors should enhance the methodological quality through registering a priori protocols, justifying selection of study designs, conducting comprehensive literature search, providing a list of excluded studies with rationales, using appropriate method for meta-analyses, and reporting funding sources among primary studies.